Efektifitas Asesmen Online Berbasis Android dengan RDev Exam Browser Metode Pieces Framework - Sutrisno, Eko; Suraji (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
The research using the PIECES Framework method aimed to evaluate the effectiveness of Android-based online assessment using the RDev ExamBrowser application at SMKN 1 Kotabesi. The student sample, selected randomly, consisted of 50 respondents. Questionnaires distributed to the students were analyzed using a Likert scale. The findings revealed that this online assessment was effective in improving student performance, providing easy access to information, saving time and costs, and ensuring good control over the exam process. The researchers suggested that implementing online assessment technology could benefit the learning evaluation process at SMKN 1 Kotabesi and recommended its broader adoption in other educational institutions.